PENGARUH PENGGUNAAN MEDIA TIMELINE TERHADAP KEMAMPUAN BERPIKIR KRONOLOGIS PEMBELAJARAN SEJARAH DI SMAN 2 METRO - Mala Citra Dara; Elis Setiawati (HISTORIA : Jurnal Program Studi Pendidikan Sejarah, 2017)
The purpose of this study to determine the influence of media on the ability to think a chronological timeline of history teaching students of class XI IPS SMAN 2 Metro Academic Year 2016-2017. This research uses quasi-experimental research (quasi exsperiment), while the design (design) research used in this study is Nonequivalent control group design. The population in this study were all students of class XI IPS SMAN 2 second semester Metro, research using sampling methods clusterrondom sampling. Thus, in this study researchers randomly pick a class (any) in the sampling. Class XI IPS 2 by the number of students 30 as an experimental class, the class XI IPS 1 number of students grade 28 as a trial, and class XI IPS 4 with the number of students 31 as the control class. There were positive and significant influence on media use a chronological timeline of the history of students' thinking ability Class XI IPS SMAN 2 Metro. Based on the analysis of the findings of instructional media use a chronological timeline of the history student thinks that has been obtained, it is concluded that the selected learning media timeline positive effect of increasing students' ability to think chronological history.